Public Sentinel : News Media and Governance Reform - Norris, Pippa (World Bank, 2012)
Do the news media especially if they are free, plural and independent of government control have an impact on the quality of governance? To many, the answer to that question is not only obvious, it is blindingly so. The news media have contributed to the improvement of governance in several countries, especially through their ability to expose corrupt deeds and speak truth to power. The problem, however, is that as the governance reform agenda evolves in the field of international development, the role of the news media is still uncertain. Opportunities to strengthen the news media will always depend on the situation in each country, and will always depend on the interplay of forces within each country. In other words, the political economic realities will always determine what can be achieved. What that means is that those who want to improve media systems in their own countries must learn to build effective coalitions. That is where work is really needed. Nonetheless, it is possible to do two things. First, it is possible to bring together how the news media can contribute to good governance outcomes. Second, it is possible to draw the necessary policy implications. This book will contribute to a greater awareness of the potential contributions of independent news media to governance reform efforts around the world.